2007
DOI: 10.1620/tjem.211.49
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Willingness to Use Complementary and Alternative Therapies for Cancer Patients: Istanbul Survey

Abstract: It is important for student nurses to be knowledgeable of the complementary and alternative therapies and to provide accurate information to both cancer patients and other health care professionals. This study examined the nursing students' willingness to use these therapies, availability of sources of information, use of the therapies for self care, opinions about the integration of these therapies into nursing curriculum, and analyzed the differences among the responses. A self-administered questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In Turkey, despite widespread consumer use, there have only been two studies of nursing students on CAM. In one study related to nursing schools, Öztekin et al [18] surveyed 640 nursing students, and noted that approximately half of the students used alternative therapies, which included massage, music therapy, and nutritional therapy. A previous study conducted by Uzun and Tan [19], which dealt with nursing students' (n = 276) knowledge of CAM therapies, found that students held positive opinions about CAM therapies, but their personal knowledge of them was limited.…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, despite widespread consumer use, there have only been two studies of nursing students on CAM. In one study related to nursing schools, Öztekin et al [18] surveyed 640 nursing students, and noted that approximately half of the students used alternative therapies, which included massage, music therapy, and nutritional therapy. A previous study conducted by Uzun and Tan [19], which dealt with nursing students' (n = 276) knowledge of CAM therapies, found that students held positive opinions about CAM therapies, but their personal knowledge of them was limited.…”
Section: Introductionmentioning
confidence: 99%
“…Hessig et al (26) also showed that education can increase the knowledge of nurses and integration on complementary therapies including music therapy. In a survey of 640 nursing students in Istanbul, participants expressed a desire to integrate music therapy into nursing curriculum (27). The participants' knowledge on the effect of music therapy was generally consistent with the literature.…”
Section: Discussionmentioning
confidence: 52%
“…Developing a knowledge base on music therapy during undergraduate nursing education is important and helps student nurses to proceed from beginner status to expert status in nursing graduation. Then, student nurses may be able to determinate which type of music would be more appropriate for patients and for themselves and offer recommendations accordingly (Oztekin et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many nursing researchers have considered including education on alternative complementary therapies as music therapy in the nursing curriculum (Oztekin et al 2007;Mei-Ying et al 2004;Dutta et al 2003). Students reported the importance of curricular change for fully integrating alternative therapies in nursing programs at all levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation